Dimensi Spiritualitas dalam Kitab Al-Fūyūḍāt Al-Rabbāniyyah bi Tafsīr Ba’ḍi Al-Āyāt Al-Qurʼāniyyah Karya Ahmad Ibn Idris - Ahmad Hudori (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2020)
This study describes spirituality in classical exegesis literature as an interesting field of study, especially when describing the interpretation of certain figures. The purpose of this research is to find out the spiritual dimension inscribed by Ahmad ibn Idris, a figure of Sufism in the XVIII M century in Morocco, in his tafsir work al-Fūyūḍāt al-Rabbāniyyah bi Tafsīr Ba'ḍi al-Āyāt al-Qurʼāniyyah. This study concludes that there are three spiritual dimensions contained in surah al-Fātiḥah, namely the dimensions of practicing worship, attachment, and universality. These three dimensions have an effect on the great potential in humans. Judging from the perspective of Ahmad ibn Idris in his tafsir book al-Fūyūḍāt al-Rabbāniyyah bi Tafsīr Ba'ḍi al-Āyāt al-Qurʼāniyyah these dimensions are contained in surah al[1]Fātiḥah from verses 13-, part of the dimensions of Worship practice, then verse 4 -5 parts of the dimension of attachment, and verses 67- of the dimension of universal.